2019
DOI: 10.3390/su11195541
|View full text |Cite
|
Sign up to set email alerts
|

Local Clusters as “Building Blocks” for Smart Specialization Strategies: A Dynamic SWOT Analysis Application in the Case of San Diego (US)

Abstract: The paper aimed at exploring the role of local industrial clusters as a part of an important evidence-based pathway for operationalizing smart specialization policy. Hitherto, the scientific debate has been largely focused on the relationship of clusters with the local business environment to boost competitiveness and has mostly searched for the operationalization of smart specialization policy in economically successful regions. However, the understanding of the role of local clusters (LCs), in terms of clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…In the second stage of the research, the Dynamic SWOT analysis was applied [ 23 ]. The framework of the Dynamic SWOT is presented later in this section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second stage of the research, the Dynamic SWOT analysis was applied [ 23 ]. The framework of the Dynamic SWOT is presented later in this section.…”
Section: Methodsmentioning
confidence: 99%
“…This concept was derived from the framework established by Bezzi [ 22 ]. Secondly, a Dynamic Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis framework is used to predict the results of the implementation of models in public policy [ 23 ], in this case, the implementation of HB-HTA in response to the dynamics of the healthcare system. The Dynamic SWOT framework provides evidence of the interdependency between the strengths and weaknesses of the HB-HTA model and the opportunities and threats resulting from the system-based conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of research and problem statement.General aspects of the study of scientific and practical problems of strategic management development in the cluster have been the subject of research by a number of scientists. In particular, Kuei-Hsien Niu, Grant Miles, Chung-Shing Lee studied the strategic development of network clusters in the context of global competitiveness [1], C. Bevilacqua, I. G. Anversa, G. Cantafio and P. Pizzimenti investigated local cluster strategies [2], J. S. Tsertseil considered the mechanisms of strategic management of the petrochemical cluster in the Republic of Tatarstan [3], K. B. Dobrova conducted a comprehensive study of financial and economic aspects of strategic management of industrial clusters [4], O. V. Kostenko analyzed methodological approaches to building a cluster development strategy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Tsangas et al [4] employed a set of indicators such as SWOT analyse to assess the sustainability of the new sector. Bevilacqua et al [5] reported that a SWOT analysis provides interesting insights toward building this conceptual framework. Jeleski et al [6] employed a SWOT analysis to classify factors that influence the smart management of RES potential, specifically household decisions about switching to renewable energy sources.…”
Section: Introductionmentioning
confidence: 99%